A new species of Centaurea sect. Acrocentron (Asteraceae, Cardueae) from Iran - Negaresh, Kazem; Yousefi, Zohreh; Kaya, Yusuf (Phytotaxa, 2023)
Centaurea serowensis Negaresh, a new species of C. sect. Acrocentron from the West Azerbaijan Province of NW Iran, is described and illustrated. Diagnostic morphological characters of this and closely related taxa are discussed and presented. The ecology and conservation status of the new species are discussed. The geographic distribution of the new species and closely related species is also presented and mapped. In addition, a taxonomic key to the species of C. sect. Acrocentron in Iran is provided.